2014
DOI: 10.1371/journal.pone.0115799
|View full text |Cite
|
Sign up to set email alerts
|

Core Self-Evaluation and Burnout among Nurses: The Mediating Role of Coping Styles

Abstract: ObjectivesThis study aimed to determine the potential association between core self-evaluation and the burnout syndrome among Chinese nurses, and the mediating role of coping styles in this relationship.MethodsA cross-sectional survey was conducted in Shenyang, China, from May to July, 2013. A questionnaire which consisted of the Maslach Burnout Inventory-General Survey (MBI-GS), the Core Self-Evaluation Scale (CSE), and the Simplified Coping Style Questionnaire (CSQ), was completed by a total of 1,559 nurses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 33 publications
(39 reference statements)
14
65
0
3
Order By: Relevance
“…In our study, gender played a significant role in emotional exhaustion reported by nurses, and female nurses reported higher levels of emotional exhaustion than male nurses. The same results have been found in several other studies as well (Amiri et al, ; Li et al, ). However, few studies found higher levels of emotional exhaustion among male nurses (Lin, Jiang, & Lam, ) and some studies did not find a significant relation between exhaustion and gender (Guo et al, ; Schadenhofer, Kundi, Abrahamian, Stummer, & Kautzky‐Willer, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, gender played a significant role in emotional exhaustion reported by nurses, and female nurses reported higher levels of emotional exhaustion than male nurses. The same results have been found in several other studies as well (Amiri et al, ; Li et al, ). However, few studies found higher levels of emotional exhaustion among male nurses (Lin, Jiang, & Lam, ) and some studies did not find a significant relation between exhaustion and gender (Guo et al, ; Schadenhofer, Kundi, Abrahamian, Stummer, & Kautzky‐Willer, ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been observed among oncology employees in Turkey, and age was negatively related to emotional exhaustion (Demirci et al, ). Li, Guan, Chang, and Zhang () also indicated that older nurses were less vulnerable to emotional exhaustion (Li et al, ). This relation maybe because younger nurses have less confidence and experience, and cannot cope with the emotional stress such as suffering or even death of patients which are common in nursing and are more affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the burnout symptoms, emotional exhaustion was the most frequently reported, which is consistent with findings of previous studies of telephone operators (Xu et al 2010), but different from results of studies of health promoters, in which the most frequently reported symptom was reduced personal accomplishment (Wang et al, 2012a;Wang et al, 2012b;Li et al, 2014). This difference may due to the sample characteristics and the nature of the work in both occupations.…”
Section: Discussionsupporting
confidence: 72%
“…Lo anterior es importante destacarlo, debido a que ambas son variables de gran interés para la formación de los profesionales de Enfermería porque permiten soportar pesadas jornadas laborales, pocas oportunidades de crecimiento y bajos salarios, que impactan el bienestar emocional y desempeño profesional (Ozkara, 2015), así como altos niveles de estrés (Guppy y Gutteridge, 1991), y las amenazas del síndrome de burnout (Lee y Akhtar, 2011;Görgens-Ekermans y Brand, 2012;Breen y Sweeney, 2013;Li, Guan, Chang y Zhang, 2014); por consiguiente, deben ser promovidas de manera conjunta desde la psicología positiva dentro de la formación de profesionales de enfermería intercultural; sin embargo, para que suceda plenamente se requiere conocer antes cómo se relacionan ambas variables, de lo que surge como pregunta de investigación ¿cómo se relacionan la autoestima y la felicidad con estudiantes de enfermería intercultural?…”
Section: Autoestima Y Felicidad En La Enfermería Interculturalunclassified